One-year Outcomes of Permanent Pacemaker Implantation after Transcatheter Aortic Valve Replacement: CONDUCT Registry: A Propensity Score-Matched Comparison - Droppa, Michal; Geisler, Tobias; Baan, Jans; Nielsen, Niels-Erik; Baranowski, Jacek; Wesselink, Wilbert; Kurucova, Jana; Hack, Luis; Vijayan, Anjaly; Bramlage, Peter; Rudolph, Tanja K (Arrhythmia & electrophysiology review, 2025)
OBJECTIVES: The occurrence of new conduction abnormalities necessitating permanent pacemaker implantation (PPI) is a complication of transcatheter aortic valve replacement (TAVR). Previous studies have shown inconsistent results about the clinical impact of new PPI after TAVR. METHODS: CONDUCT was a prospective observational registry that enrolled 295 patients undergoing TAVR at four European centres. The primary goal of this registry was to compare 1-year clinical outcomes in TAVR patients with or without PPI, using one-to-four propensity score matched (PSM) analysis. It also assessed major adverse cardiac events (MACE) in patients undergoing right ventricular pacing after PPI. RESULTS: Out of 160 PSM patients, 36 underwent PPI and the other 124 had no PPI within 30 days post-TAVR. The median age of the patients was 80 years, with more men (80.6% and 84.7% in patients with and without PPI, respectively) and similar EuroSCORE II and Society of Thoracic Surgeons scores. Patients with PPI had higher diabetes prevalence (p=0.055) and lower left ventricular ejection fraction percentages (p=0.034), but higher systolic pulmonary artery pressure (p=0.013) than those without PPI. However, these differences diminished after PSM. At 1 year, PPI patients had a nonsignificant but slightly higher incidence of MACE (22.2% versus 13.7%; p=0.216) (HR 1.63; 95% CI [0.72-3.71]) driven by increased heart failure (11.1% versus 2.4%; p=0.046) (HR 5.05; 95% CI [1.09-23.4]). Freedom from all-cause mortality, cardiovascular death, stroke and endocarditis at 1-year follow-up was comparable between groups. CONCLUSION: Despite a higher incidence of congestive heart failure rehospitalisation in patients undergoing PPI, 1-year clinical outcomes were similar in both groups.
Keywords: permanent pacemaker implantation; Aortic stenosis; transcatheter aortic valve replacement